Civil society in the Philippines : theoretical, methodological and policy debates - Clarke, Gerard, 1965- (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
"Using the case study of the Philippines, this book provides a path-breaking account of civil society. Critically engaging with theoretical, methodological and policy debates on the analysis of civil society in the development studies, political science and sociology literature, it offers a comprehensive, multi-disciplinary, empirically-based, and national-level portrait of civil society. In challenging the widespread belief that civil society is an institutional arena in which the poor and marginalized can challenge and reverse their social, economic and political disempowerment, the book argues that civil society is characterised by structural inequalities that echo spatial and income inequalities. It thus compounds poverty and primarily empowers urban-based professionals and their families. Focusing on the Philippines, a country renowned for a vibrant civil society which first emerged under American colonial rule (1898-1946) and which re-emerged from 1986 after 14 years of authoritarian rule, the book traces the reasons for this extensive civil society and it's [sic] political, economic and social implications, and draws comparison to other developing countries"--Supplied by publisher.
Civil society, democracy and (in)equality -- Civil society and the challenge of statistical capture -- The shaping of Philippine civil society in legislation and government policy -- The statistical contours of Philippine civil society -- The social origins of Philippine civil society, 1571-1946 -- The social consolidation of Philippine civil society, 1946-2010.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Civil society -- Philippines; Social justice -- Philippines; Power (Social sciences) -- Philippines; Economic development -- Social aspects -- Philippines; Philippines -- Social conditions; Electronic books